The Influence of Using Technology to Accomplish Work-related Tasks Online - AlFahl, Husam (Jordan Journal of Business Administration, 2023)
People are using electronic and mobile devices extensively for many purposes ranging from recreation to accomplishing work at anytime from anywhere and such practice comes to be a significant part of their lifestyles. Indeed, many employees working remotely can achieve their work-related tasks through electronic devices even though these devices pose potential threats to the work-life balance. The current paper attempts to investigate the influence of using technology to accomplish work-related tasks online. To validate the research model, structural equation modeling was applied. Employees in Saudi Arabia working in organizations were requested to participate in filling the research questionnaire to test the research hypotheses. The findings disclosed that using technology to accomplish work-related tasks online has negative effects on the employees. The results of the study showed that the addiction to the usage of technologies to accomplish work-related tasks increases the perceived work overload, resulting in an increased work-life balance disruption.